Lanzarote como figura Crística: Misticismo y sacrificio en El caballero de la carreta de Chrétien de Troyes. - ROCA TICÓ, XAVIER (Scripta)
This article examines how Chrétien de Troyes portrays Lancelot as a Christ-like figure in Lancelot, the Knight of the Cart. Lancelot's self-denial in riding the cart, the antithesis between the land of Logres and the Land of Gorre, his encounter with the Lance of Longinus, the mystery of the marble slab that only he can move, and his passage over the sword bridge, during which stigmata appear on his body, are elements that consolidate his image as a redeemer. These aspects symbolize his sacrifice and redemptive mission, highlighting Chrétien de Troyes' ability to intertwine religion and literature in a narrative that is deeply spiritual and symbolic.